Village-level decentralisation of judicial system: Desirability and advantages - Mahi Pal (1999)
The author picks up for discussion the case of Nyay Panchayats as a viable form of decentralised judicial system at the village level. Besides giving a historical perspective on its evolution since pre-independence period, he discusses position of Nyay Panchayats under 73rd Constitutional Amendment Act and provisions therefor under State Panchayat Acts. He then discusses the desirability of a robust Nyay Panchayat system and, to realise it on sustainable basis, suggests bringing up another Constitutional amendment. - Reproduced
Keywords: Judiciary - India; Judiciary